Transborder Gene Flow between Canada and the USA and Fine‐Scale Population Structure of Atlantic Cod in the Broader Gulf of Maine Region. Issue 5 (10th June 2021) - Puncher, Gregory Neils; Wang, Yanjun; Martin, Ryan; DeCelles, Gregory; Cadrin, Steven X.; Zemeckis, Douglas; Rowe, Sherrylynn; Leblanc, Nathalie M.; Parent, Genevieve J.; Pavey, Scott A.
Abstract: Fishery managers have struggled for decades to rebuild stocks of Atlantic Cod Gadus morhua in the northwestern Atlantic Ocean, and the resolution of current fine‐scale population structure will surely help those efforts. Using double digest restriction‐site associated DNA sequencing, we analyzed 248 adult and 215 juvenile Atlantic Cod collected from areas bordering the Canada–USA boundary in 2017–2018. Chromosomal inversions from linkage group (LG) 2 and LG 7 contribute the largest amount of variance to the data set. A southwesterly decrease in the proportion of LG 1 inversion haplotypes may indicate gene flow from areas north of 45°N. Samples from both the northern Gulf of Maine and Bay of Fundy were genetically distinct from all other samples, suggesting that local spawning groups may still be active. Genetic similarities between Atlantic Cod from Browns Bank and eastern Georges Bank indicate that transborder gene flow is ongoing. These results will help to better define the stocks in order to guide the implementation of management strategies in the USA and Canada, which should consider rebuilding exhausted and genetically isolated populations.